Wool - Howey, Hugh. (New York : Simon & Schuster Paperbacks, 2013)
In a future toxic landscape, a community that lives in an underground silo is rocked by the desire of Sheriff Holston, who has upheld the group's rules for years, to go outside, setting in motion events that kindle the fire of revolution.
"Previously published in serial form by Broad Reach Publishing/Amazon Digital Services, Inc."--T.p. verso.
Keywords: Underground areas -- Fiction; Civilization, Subterranean -- Fiction; Sheriffs -- Fiction; Revolutions -- Fiction; Dystopias; Science fiction